Pengaruh Kepadatan Kandang Terhadap Komposisi Fisik Ayam Broiler CP 707 - Dominggus Dewa Dato; Ni Made Ayu Gemuh Rasa Astiti; Ni Ketut Sri Rukmini (GEMA AGRO, 2019)
The aim of this research was to determine the effect of different density of cages on the physical composition of the breast carcass and thighs of CP 707 broiler chickens. Cage and density of cages are important elements in the business of chicken farming. Cage density that is too high or too low can affect the temperature and humidity of the air in the cage and will ultimately affect the growth of the carcass. This study uses a completely randomized design (CRD) with 3 treatments. The treatments of P1 were 8 heads/m2, P2 density was 10 heads/m2, and P3 12 heads/m2 each treatment was repeated 3 times. The parameters observed were the physical composition of the carcass of the chest, upper thigh and lower thigh. The data obtained were analyzed by variance, if the data obtained were significantly different (P <0,05), it would be continued with the multiple distance test from Duncan. The results showed the density of the cages of 8,10, and 12 tails/m2 did not affect the physical composition of the carcass of the thigh both upper and lower thighs, but the density of the cage of 12 tails/m2 significantly affected the physical composition of the carcass of the chest especially the meat and chicken breast bones CP 707 broiler.